Amoebic Anal Fistula: New Insight Into an Old Disease - Vivek Agrawal; Pankaj Kumar Garg; Bhupendra Kumar Jain; Kiran Mishra; Debajyoti Mohanty (Acta Medica Indonesiana)
A 67-year-old gentleman underwent fistulectomy for low trans-sphincteric anal fistula along with curettage for an associated abscess extending proximally for half a centimeter into the intersphincteric plane. The roof of the cavity became clearly visible after satisfactory culmination of the surgical procedure. Histopathological examination of the fistulous tract and the curetted granulation tissue revealed presence of multiple trophozoites of Entamoeba histolytica exhibiting erythrophagocytosis in the background of mixed inflammatory infiltrate. This case report provides the outlook that yields the novel insight into the possible role of Entamoeba histolytica in the pathogenesis and persistence of the fistulous tract.